Impact of silicone and metal port-a-cath implants on superficial hyperthermia treatment quality. (February 2015) - Trujillo-Romero, Citlalli Jessica; Paulides, Margarethus Marius; Drizdal, Tomas; van Rhoon, Gerard C.
Abstract Purpose: A port-a-cath is a device implanted under the skin for continuous drug administration. It is composed of a catheter and a silicone or metal reservoir. A simulation study was done to assess the impact of a port-a-cath implant on the quality of superficial hyperthermia treatments applied using the Lucite cone applicator (LCA). Methods: Specific absorption rate (SAR) and temperature distributions were predicted using SEMCAD-X (version 14.8). We simulated 72 arrangements: two LCA-implant set-ups (central port-a-cath or at an edge below the LCA footprint), six translations of the LCA per set-up, two LCA orientations (Parallel or perpendicular electric field direction) per set-up, two implant materials (silicon or metal) and a control without port-a-cath. Treatment quality was quantified by the average 1 g SAR coverage (CV25%), i.e. volume within the 25% iso-SAR surface, and the volume within the 40 °C iso-temperature surface (CV40 °C). Results: CV25% reduced with a silicon port-a-cath located below the LCA footprint. In the worst scenario, only 64% of the CV25% of the control set-up was achieved. For a metal port-a-cath below the LCA aperture, dramatic reductions of CV25% were predicted: worst scenario down to 12.1% of the control CV25%. For the CV40 °C the worst case values were 74.5% and 6.5%, for silicon and metal implants, respectively. Conclusions: A silicone port-a-cath below the LCA had a smaller effect on treatment quality than a metal implant. Based on this study we recommend verifying heating quality by 3D patient-specific treatment planning when a port-a-cath is located below the footprint of the applicator.